1982
DOI: 10.1111/j.1440-6055.1982.tb01784.x
|View full text |Cite
|
Sign up to set email alerts
|

A TECHNIQUE FOR RECORDING EFFERENT NEURONE ACTIVITY FROM NORMAL AND POISONED CATTLE TICKS [BOOPHILUS MICROPLUS (CANESTRINI)]

Abstract: A technique is described for obtaining action potentials from tick efferent nerves. Electrical stimulation of the synganglion was shown to be promising for the investigation of tick motor neurone activity. With the continuously perfused suction electrode technique distinct effects on action potential frequency were obtained, following exposure to different groups of cbemicals. These results are discussed on the basis of what is known of the neurochemistry of ticks and the mode of action of the chemicals concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Most studies in ticks investigating the ACh receptor (AChR) to date have concentrated on the muscarinic AChR (mAChR). Binnington and Rice (1982) showed that pilocarpine, a mAChR agonist, produced a marked increase in action potential frequency in haemal and salivary nerves in B. microplus, suggesting the presence of the mAChR in the central nervous system. Also, pilocarpine and arecoline severely reduced oviposition when injected into engorged B. microplus (Booth 1989).…”
Section: Cholinergic Systemmentioning
confidence: 98%
“…Most studies in ticks investigating the ACh receptor (AChR) to date have concentrated on the muscarinic AChR (mAChR). Binnington and Rice (1982) showed that pilocarpine, a mAChR agonist, produced a marked increase in action potential frequency in haemal and salivary nerves in B. microplus, suggesting the presence of the mAChR in the central nervous system. Also, pilocarpine and arecoline severely reduced oviposition when injected into engorged B. microplus (Booth 1989).…”
Section: Cholinergic Systemmentioning
confidence: 98%
“…The other line of evidence for muscarinic ACh receptors comes from physiological experiments in which spontaneous spikes (action potentials) were recorded, with an extracellular suction electrode, from nerves of the synganglion of adult B. microplus (Binnington & Rice, 1982). Application of the muscarinic agonist, pilocarpine, to the synganglion at 10~5 M increased the spontaneous spiking activity in both haemal and salivary nerves.…”
Section: Introductionmentioning
confidence: 99%